A Structural VAR Approach to Estimating Budget Balance Targets - Robert A Buckle; Kunhong Kim; Julie Tam (New Zealand Government, The Treasury, 2001)
The Fiscal Responsibility Act 1994 states that, as a principle of responsible fiscal management, a New Zealand government should ensure total Crown debt is at a prudent level by ensuring total operating expenses do not exceed total operating revenues. In this paper a structural VAR model is estimated to evaluate the impact on the government's cash operating surplus (or budget balance) of four independent disturbances: supply, fiscal, real private demand, and nominal disturbances. Based on the distribution of these disturbances, stochastic simulations are undertaken to derive the level of the ex ante cash budget balance needed to achieve an actual cash budget balance, at a given level of probability, at some future time horizon.
Keywords: C51; E62; H61; 330; Budget target; Fiscal policy; Fiscal Responsibility Act; Structural VAR; Stochastic Simulation